1999
DOI: 10.1016/s0035-9203(99)90176-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Leishmania braziliensis in naturally infected individual sandflies by the polymerase chain reaction

Abstract: The natural infection of sandflies by Leishmania in wild-caught specimens was studied, using the polymerase chain reaction (PCR)-hybridization technique. The PCR was carried out using 2 oligonucleotides (primers 3J1 and 3J2) derived from a repetitive nuclear DNA sequence. The primers support the enzymatic amplification of a fragment of approximately 500 bp, present in the nuclear DNA of Leishmania braziliensis. The expected band was observed in 5 of 65 sandflies containing flagellates. After hybridization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
1
11

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 11 publications
1
31
1
11
Order By: Relevance
“…Based on the results of the current work, the use of Shannon traps allowed us to evaluate the presence of some species that were not collected (Passos et al 1993) and it has been shown to be highly sensitive in detecting protozoa parasites into phlebotomine sand flies (Rodriguez et al 1999, Miranda et al 2002, Michalsky et al 2002. Nevertheless, previous reports have shown that phlebotomine infectivity rates in nature are low, 0.2 to 2%, making the parasite finding difficult (Rodriguez et al 1999, Miranda et al 2002.…”
Section: Discussionmentioning
confidence: 83%
“…Based on the results of the current work, the use of Shannon traps allowed us to evaluate the presence of some species that were not collected (Passos et al 1993) and it has been shown to be highly sensitive in detecting protozoa parasites into phlebotomine sand flies (Rodriguez et al 1999, Miranda et al 2002, Michalsky et al 2002. Nevertheless, previous reports have shown that phlebotomine infectivity rates in nature are low, 0.2 to 2%, making the parasite finding difficult (Rodriguez et al 1999, Miranda et al 2002.…”
Section: Discussionmentioning
confidence: 83%
“…mexicana DNA sample or any other negative controls previously mentioned. PCR and hybridization are very useful techniques for species specific identification of parasites in naturally infected sandflies as was previously demonstrated by Rodriguez et al (1999) mainly when parasites in the gut of the specimen are not very abundant. Here we report the utility of primers and probe derived from the nuclear DNA (Rodriguez et al, 1997) in the specific identification of Le.…”
Section: Discussionmentioning
confidence: 98%
“…Leishmania identification was carried out according to Rodriguez et al (1999). The samples were heated for one hour at 56 o C, and the DNA was extracted with The DNA probe was labelled using the digoxigenin-anti digoxigenin kit (Boehringer-Mannhein, Germany) according to the instructions of the manufacturer.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Actualmente, la detección de parásitos del género Leishmania en los insectos incluye métodos que van desde la búsqueda directa de los flagelados en el tracto digestivo del insecto hasta técnicas moleculares que usan principalmente K ADN (12,(26)(27)(28)(29)(30). La técnica de reacción en cadena de la polimerasa (PCR), por su alta sensibilidad y especificidad, ha facilitado adelantar estudios ecoepidemiológicos en áreas de alta endemicidad, suministrando datos más precisos en periodos de tiempo más cortos (17,29).…”
Section: Discussionunclassified